STRATEGI PEMASARAN DIGITAL BERBASIS MEDIA SOSIAL DALAM MENINGKATKAN ENGAGEMENT KONSUMEN DI ERA METAVERSE - Harry Brahmana; Hommy Dorthy Ellyany Sinaga (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The development of digital technology has drastically changed the way we do marketing, one of which is by utilizing the metaverse as a new interactive platform to create relationships between consumers and brands. This study aims to explore digital marketing strategies based on social media in facing the metaverse era, focusing on innovative approaches, user interactions, and their influence on the effectiveness of marketing campaigns. The method used in this study is a literature study with a qualitative narrative approach, referring to various recent scientific sources that discuss the integration of digital technology, social media, and virtual space. The findings show that the metaverse provides extensive opportunities to personalize consumer experiences through the use of avatars, virtual reality, and interactions in communities. Now, digital marketing strategies must go beyond ordinary visual content and turn into comprehensive experiences that involve participation. However, there are challenges that arise in technical aspects, data protection, and the digital access gap that need to be addressed.